Harnessing digital health technologies and real-world evidence to enhance clinical research and patient outcomes - Shreyash Mahadik; Prerona Sen; Ekta J. Shah (Digital Health)
The intersection of digital health technologies (DHT) and real-world evidence (RWE) is redefining the landscape of clinical research and regulatory science, offering unique opportunities to improve drug development, patient monitoring, and evidence-based decision-making. The extensive use of digital technologies has facilitated continuous, real-time health data collection, while RWE helps bridge the gap between controlled clinical trials and real-world patient experiences. As healthcare systems progressively integrate these various data sources, they are reshaping regulatory approval processes and enhancing post-market surveillance of therapies. Furthermore, advancements in the integration of artificial intelligence and the application of pharmacogenomics results in more effective, efficient, and personalized healthcare delivery. Nonetheless, these developments are met with critical challenges, and the lack of standardized global regulatory frameworks creates disparities in how this data is utilized across jurisdictions. Addressing these limitations through robust validation frameworks, harmonized regulatory policies, and interdisciplinary collaboration is essential to realizing the complete potential of DHT and RWE in precision medicine applications. This review examines the opportunities, challenges, and future directions of merging DHT and RWE to enhance precision medicine, emphasizing the importance of collaboration among researchers, regulators, and healthcare providers.